You have (+8) + (-15) = -(15 - 8)

The result of this is -7 because you simplify the expression as follows:

(+8) + (-15)

remove the brackets, as the sign before (-15) is +, eliminate it without altering -15.

=> 8 - 15

=> -7

[ If there is...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You have (+8) + (-15) = -(15 - 8)

The result of this is -7 because you simplify the expression as follows:

(+8) + (-15)

remove the brackets, as the sign before (-15) is +, eliminate it without altering -15.

=> 8 - 15

=> -7

[ If there is a minus sign before the brackets, when the brackets are opened the sign of all the terms in the brackets are reversed, else for a plus sign before the brackets they remain the same. ]

Here the terms 8 and -15 are being added, the result will be a negative number given that 15 > 8 and equal to 7 as 15 - 8 = 7.

Hope the explanation helped.

**The result of (+8) + (-15) = -7**

We will verify that the correct answer to (8) + (-15) = -(15-8) is -7.

=> (8) + (-15) = -(7)

=> 8 - 15 = -7

=> -7 = - 7

**(8) + (-15) = -(15 -8) has been verified.**

**The correct simplification is -7.**